Hogsbackia africaensis gen. nov., sp. nov. (Acari, Oribatida, Ceratozetoidea, Punctoribatidae), from Afromontane forest of South Africa - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A.; Behan-Pelletier, Valerie M. (Zootaxa, 2021)
A new oribatid mite genus, Hogsbackia gen. nov. (Oribatida, Punctoribatidae), with type species Hogsbackia africaensis sp. nov., is proposed and described from the indigenous Afromontane forest of South Africa. The new genus is closely related to Scotiazetes, from which it is most easily distinguished by body size ratio, number of notogastral and genital setae, type of humeral porose area Ah, position of dorsophragmata, and leg setation. The redescription of Scotiazetes bidens Wallwork, 1966 is presented, based on material from South Georgia (Antarctic region). The generic diagnosis of Scotiazetes is revised, and the genus is transferred from Ceratozetidae to Punctoribatidae. Relationships between the genera Hogsbackia gen. nov., Scotiazetes and other punctoribatid genera are discussed.